An electrospun flexible Janus nanoribbon array endowed with simultaneously tuned trifunctionality of electrically conductive anisotropy, photoluminescence and magnetism. (27th October 2017) - Tian, Jiao; Ma, Qianli; Yu, Wensheng; Dong, Xiangting; Yang, Ying; Zhao, Bo; Wang, Jinxian; Liu, Guixia
Abstract : A flexible Janus nanoribbon array endowed with simultaneously tuned trifunctionality of electrically conductive anisotropy, photoluminescence, and magnetism was fabricated by electrospinning. Abstract : Herein, a novel structured Janus nanoribbon array, {[Dy(BA)3 phen + Eu(BA)3 phen]/PMMA}//[PANI/Fe3 O4 /PMMA], possessing tunable anisotropic electrical conduction, photoluminescence, and magnetism was successfully prepared by electrospinning technology using a parallel spinneret. Every single Janus nanoribbon comprises PANI, Fe3 O4 NPs, and PMMA as a conductive and magnetic side and Dy(BA)3 phen and Eu(BA)3 phen complexes and PMMA as an insulating and photoluminescent side. The emission color of the Janus nanoribbons array excited by 275 nm ultraviolet light could be oriented in an extensive range of yellow–orange–red color by modulating the contents of rare earth complexes, PANI or Fe3 O4 NPs. Furthermore, electrically conductive anisotropy of the Janus nanoribbon array can be tuned by modulating the PANI content, and the conductance ratio of the directions parallel and perpendicular with respect to the length of the Janus nanoribbon varies from 10 4 to 10 6 . The conductance in the parallel and perpendicular direction of the Janus nanoribbon array containing 60% of PANI is about 1.8246 × 10 −4 S and 1.438 × 10 −10 S, respectively. Furthermore, the magnetic performance of the Janus nanoribbon array could be tuned by modulating the quantities of Fe3 O4 NPs. Moreover, the means of fabrication for the Janus nanoribbon array are of widespread significance for the fabrication of other anisotropically conductive films with multi-functionality.